Latinx Teachers Advocating and Providing Support to Culturally and Linguistically Diverse Students and Their Families - Pedro S Espinoza; Kay Ann Taylor (Educational Considerations, 2021)
This study explores how Latinx teachers engage in social justice agendas for their Culturally and Linguistically Diverse students, specific barriers and support systems these Latinx teachers encounter in their social justice work, and the educational strategies Latinx teachers value in their role as advocates in their social justice work. The following three themes emerged from participant data: (a) Tesoros from students and families, (b) Advocacy for CLD students: High expectations of all students, (c) Support system as pre-service and in-service teachers: hechale ganas/work hard. We briefly formulate each of these themes, providing fragments from participant testimonios as examples. After formulation and discussion of each theme, we provided recommendations for delivering support to CLD students and their families.
Keywords: Latinx Teachers; Advocate; Culturally and Linguistically Diverse; Students and Families